2018
DOI: 10.1016/j.jaci.2018.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and zinc tune autoinflammatory Toll-like receptor 4 signaling by S100A12

Abstract: This study was supported by grants from the intramural innovative medical research program of Muenster University medical faculty (grant no. KE121201 to C.K.) and the German Research Foundation (DFG, grant no. WI3176/2-1 to H.W. and grant no. Fo354/3-1 to D.F.). Disclosure of potential conflict of interest: C. Kessel & D. Foell have filed a patent application on ''means and methods for diagnosing and treating inflammatory disorders'' regarding proinflammatory S100A12 homomultimers (WO 2016/178154 A1). The rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
3
25
0
Order By: Relevance
“…On the other hand, a study by Stoll et al also confirmed TLR‐4 expression on coronary artery endothelial cells, both in vitro and by immunostaining of tissue . In a parallel study of human monocytes performed by us, we noted that CD14 serves as a coreceptor to TLR‐4 with an integral role in S100A12 signaling . While the present data support these findings, they further suggest that S100A12 signaling in the absence of membrane CD14 cannot be bypassed by the soluble form of the receptor.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…On the other hand, a study by Stoll et al also confirmed TLR‐4 expression on coronary artery endothelial cells, both in vitro and by immunostaining of tissue . In a parallel study of human monocytes performed by us, we noted that CD14 serves as a coreceptor to TLR‐4 with an integral role in S100A12 signaling . While the present data support these findings, they further suggest that S100A12 signaling in the absence of membrane CD14 cannot be bypassed by the soluble form of the receptor.…”
Section: Discussionsupporting
confidence: 81%
“…To determine whether the muted response of HCAECs to LPS and S100A12 was attributable to lower expression of TLR‐4 coreceptors, we measured the expression of CD14 both on primary human monocytes and on HCAECs, since detection of TLR‐4 agonists can involve the interaction of TLR‐4 with CD14 . As expected, our results showed that HCAECs expressed significantly lower levels of TLR‐4 compared to that in human monocytes (Figure B).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations